Effect of Nickel: Zinc ratio in nickel-zinc-ferrite nanoparticles as surfactant on recovery efficiency in enhanced oil recovery - Zaid, H.M. (Trans Tech Publications Ltd, 2014)
Integration of nanoparticles in enhanced oil recovery (EOR) has been intensively studied in recent years due to their unique properties owing to the nanoscale dimensions, rendering them to have different properties in comparison with its bulk material. Application of magnetic nanoparticles such as ferrites was able to exploit their rheological properties as a chain-like structure formed due to dipole-dipole alignment with the applied magnetic field. Ferromagnetic Cox2+Fe1-x2+ Fe23+O4 nanoparticles had shown an increment in the oil recovery under the irradiation of an EM wave. In this research, the influence of magnetic nanoparticles nickel-zinc-ferrite, Ni1-xZnxFe2O2 in the form of nanofluids on the recovery efficiency in EOR was studied. Nickelzinc- ferrite magnetic nanoparticles with various values of x were synthesized to observe the effect of nickel to zinc ratio on recovery efficiency. The nanoparticles were characterized using X-ray Diffraction (XRD) and Vibrating Sample Magnetometer (VSM). Coreflooding experiments were conducted where the nanofluids were injected into the compacted sand saturated with crude oil under EM irradiation. The amount of oil recovered from the core was evaluated. VSM tests shows that the sample with x = 0.5 had the highest magnetization of 52.6 emu/g. The nanofluids prepared from the sample also achieved the highest crude oil recovery of 26.07 of the residual oil in place (ROIP). Â© (2014) Trans Tech Publications, Switzerland.